Immediate complete denture: A case report - Tihaček-Šojić Ljiljana; Župac Luka; Miličić-Lazić Minja (Serbian Medical Society - Dental Section, Belgrade, 2022)
An immediate denture is a temporary or permanent removable denture fabricated in the presence of natural teeth. Patients diagnosed with periodontitis are usually indicated for this type of dentures. Fabrication according to the specific protocol can enhance functional, phonetic, and aesthetic rehabilitation immediately after tooth extraction. Laboratory procedures have few specificities in comparison to conventional complete dentures, but the most important one is trimming the cast according to previously examined periodontal status. Following the production protocol, it is possible to provide functional, phonetic and aesthetic rehabilitation of the patient immediately after tooth extraction. In addition, it is possible to achieve proper remodeling of the residual alveolar ridge owing to the direct contact of the denture base with the extraction wound during the consolidation period. The aim of this paper is to present clinical and laboratory procedures in the process of making immediate complete denture.